Análise de desempenho do protocolo RAW em uma rede 802.11ah - Siman, Luís Eduardo (2022)
Computer networks grow and evolve according to technological advances and the needs that arise at different times. Networks for IoT devices have specific needs, as they are often in a large area, filled with low-power devices, and especially dense, which can degrade performance when device transmissions interfere with each other. The 802.11ah network model proposes solutions for this scenario, with a medium access protocol prepared for high numbers of devices: RAW (Restricted Access Window), which groups the devices and limits access to the médium in order to reduce the number of collisions. This work proposes to analyze the RAW protocol, focusing on the impact of these groups on the performance of a network. By doing simulations and running sets of experiments, it is observed that even in considerably small networks, the protocol has a visible effect, and that it can bring great benefits to densely populated networks.